FIR filter design - Chin, Amelia May Yin (2018)
The objective of this final year project (FYP) is to investigate and evaluate design methods of Finite Impulse Response (FIR) filter. In this report, the advantages and disadvantages of diverse ways and techniques for the distinct types of FIR filter designs were explored. In which, one of the technique, window method, were chosen to be discussed with further details. The comparison and evaluation of the several types of Window methods are supported with the use of FORTRAN and MATLAB Simulink software. FORTRAN is used to compute the coefficient values for the several types of Window methods of FIR filter design. These values were then passed on to MATLAB Simulink to plot the frequency response graph. Lastly, the observation and results of FIR filter design of Window techniques are discussed and concluded.